Optimal switching pattern for space vector modulated Z-source NPC inverter - Effah, F.B.; Watson, A.J.; Wheeler, P.W.; Clare, J.C.; Sunter, S. (My University, 2012)
The Z-source inverter is a relatively recent power converter topology that has been demonstrated in the literature to exhibit voltage-buck and voltage-boost capability. The Z-source concept can be applied to two-level and multilevel inverters. However, multilevel inverters offer many benefits for higher power applications compared to two-level inverters. Previous publications have shown the control of a Z-source neutral point clamped inverter using the carrier-based modulation technique. This paper presents the optimal switching pattern for the control of a Z-source neutral point clamped inverter using the space vector modulation technique. This gives a number of benefits, in terms of implementation and harmonic performance. The adopted approach enables the operation of the Z-source arrangement to be optimised and implemented digitally without introducing any extra commutations. Simulation results are presented to verify the concepts.
6th IET International Conference on Power Electronics, Machines and Drives, PEMD 2012 -- 27 March 2012 through 29 March 2012 -- Bristol -- 91741
Keywords: Buck-boost; Neutral point clamped inverter; Space vector modulation; Z-source inverter